Predictive Ability of APACHE II Score in Phrae Hospital’s Surgical Intensive Care Unit - Chottipadiwetkul, Wichin (Journal of Health Science of Thailand, 2019)
In an retrospective analytical study, 173 patients admitted to surgical intensive care unit in Phrae hospital during August 2006 to September 2007 were classified based on the APACHE II severity of disease classification system on day one of admission. The mean APACHE II score was 9.8 (SD = 4.8) in survivors group and 16.4 (SD = 5.3) in non survivors group. No significant difference of death between patients who admitted directly to ICU or transferred from ward (p =0.942). The two most valued parameters to predicte outcome were oxygenation (p < 0.01) and body temperature (p < 0.05). The recorded death rate was correlated with the predicted rate. APACHE II score was an accurate predictor of group outcome and provided an excellent means of severity classification and should be used in surgical ICU widely.